Different Culture Media Affect Proliferation, Surface Epitope Expression, and Differentiation of Ovine MSC - Carina Adamzyk; Tanja Emonds; Julia Falkenstein; René Tolba; Wilhelm Jahnen-Dechent; Bernd Lethaus; Sabine Neuss (Hindawi Limited, 2013)
Orthopedic implants including engineered bone tissue are commonly tested in sheep. To avoid rejection of heterologous or xenogeneic cells, autologous cells are preferably used, that is, ovine mesenchymal stem cells (oMSC). Unlike human MSC, ovine MSC are not well studied regarding isolation, expansion, and characterization. Here we investigated the impact of culture media composition on growth characteristics, differentiation, and surface antigen expression of oMSC. The culture media varied in fetal calf serum (FCS) content and in the addition of supplements and/or additional epidermal growth factor (EGF). We found that FCS strongly influenced oMSC proliferation and that specific combinations of supplemental factors (MCDB-201, ITS-plus, dexamethasone, and L-ascorbic acid) determined the expression of surface epitopes. We compared two published protocols for oMSC differentiation towards the osteogenic, adipogenic, and chondrogenic fate and found (i) considerable donor to donor variations, (ii) protocol-dependent variations, and (iii) variations resulting from the preculture medium composition. Our results indicate that the isolation and culture of oMSC in different growth media are highly variable regarding oMSC phenotype and behaviour. Furthermore, variations from donor to donor critically influence growth rate, surface marker expression, and differentiation.